Classification of Circumstances that Contributed to the Commission of a Crime in the Legislation of the Russian Federation - Volkova, Galina; Ivanov, Dmitriy; Vasyukov, Vitaliy; Polyakov, Sergey; Batyukova, Vera (Jurnal Cita Hukum, 2024)
In the article, the authors consider the most pressing issues related to the classification of circumstances that contributed to the commission of a crime in Russian legislation. It is established that the factors that make it possible to classify the above circumstances are: the identity of the suspect (accused); the living conditions and upbringing of the person who committed the crime; the circle of communication of the person who committed the crime; the circumstances of the origin of criminal intent; the circumstances that made it possible to achieve criminal goals; circumstances of an objective nature, the totality of which allows you to commit a specific crime; the absence of preventive measures and preventive work in the presence of appropriate conditions. The authors substantiate the position that the considered factors, according to which the classification of the circumstances under study was carried out, are conditional and are not exhaustive in their essence. At the same time, the classification of the circumstances under consideration by the authors allows the head of the investigative body and the investigator to correctly and competently plan their daily activities aimed at identifying, proving and eliminating them. In conclusion, the authors conclude that the classification of circumstances that contributed to the commission of a crime is necessary to build an algorithm of actions to identify, prove and eliminate them at all stages of pre-trial proceedings in criminal cases. Only when all three dominants are achieved (identification, proof, elimination) will the goals of criminal proceedings be achieved.